Air transportation delay propagation analysis with uncertainty in coloured–timed Petri nets. Issue 6 (25th December 2020) - Shao, Quan; Xu, Chenchen
Abstract : In the transport management of aviation networks, uncertain factors and delay propagation are two main sources of flight delays. However, the impacts of uncertainty and the degree of delays are difficult to calculate empirically in daily operations. In this paper, a novel delay propagation model is introduced utilising the mathematical modelling tool coloured–timed Petri nets. This model enables descriptions of the delay propagation progress and flight delay calculation under the influence of uncertain factors. In order to understand the influence of airline network operations with uncertainties, the mechanisms of the main uncertainties (weather factors, air traffic control (ATC) factors and other low-probability random factors) are studied and probability functions are obtained. To simulate conditions under different uncertainties, experiments were carried out on an aviation network comprising 13 airports under different settings of bad weather and ATC. The simulation results revealed the influence of different uncertain factors, delay propagation time through flight chains and delay prediction in the aviation network. Based on the predicted flight delays, flight sequence update rules were established, which showed that the updated flight sequence significantly reduced flight delays compared with the original flight sequence.